Análisis del discurso antisistema de la cultura urbana punk en Quito. - Zapata Lozano, Juan Carlos. (2015)
This article explores the mechanism, elements and resources that build a countersystem discourse of punks in Quito, since interviews of two generations of young punks from Quito, in which evidenced the characteristic elements, creators of discourse. The body narrative, the music and use of phraseologisms, they are analyzed that identifying characteristics of this urban culture as from the same young people build a counterhegemonic discourse, from clothing, Kinesics and proxemics, the influence of lyrics to create your own language code to communicate and relate with others punks. Finally analyzed the role of the society against punk discourse, which it is discriminatory, explains the new discrimination forms to this movement and I reflect on the right to use public spaces and build intercultural.